Enhancing preservice teachers’ collaborative problem solving through STEM project-based learning - Fitriani, Rita; Suwono, Hadi; Ibrohim, Ibrohim; Lukiati, Betty (Institute of Advanced Engineering and Science, 2025)
This study aimed to determine the effect of science, technology, engineering, and mathematics project-based learning (STEM-PjBL) on the collaborative problem solving (CPS) of preservice teachers (PSTs). The pretest-posttest non-equivalent control group design was employed. A total of 72 PSTs enrolled in plant physiology course participated in this study. Self-assessment and project were used to evaluate PSTs’ CPS skills. Self-assessment scores were analyzed by analysis of covariance (ANCOVA), while project scores were analyzed by the Mann-Whitney U test. The results of self-assessment indicated that STEM-PjBL enhances CPS skills, particularly in social regulation, task regulation, and knowledge building. The results of the team’s problem-solving skills in completing the project did not differ between the two groups. But the result of integrated STEM skills showed that the STEM-PjBL group was better at integrating STEM disciplines into their project. This study highlights the importance of interdisciplinary projects in a PjBL environment that can be adopted by teacher preparation programs for enhancing PSTs’ CPS skills as well as gaining knowledge of STEM integration.